300 MPa grade biodegradable high-strength ductile low-alloy (BHSDLA) Zn-Mn-Mg alloys: An in vitro study. (1st March 2023) - Shi, Zhang-Zhi; Li, Xiang-Min; Yao, Sheng-Lian; Tang, Yun-Zhi; Ji, Xiao-Jing; Wang, Qiang; Gao, Xi-Xian; Wang, Lu-Ning
Highlights: Developed ductile Zn-Mn-Mg alloys with yield strengths > 300 MPa. The alloys exhibit corrosion rates from 38 to 78 µm y –1 in SBF. The alloys show good cytocompatibility for MC3T3-E1 cells. They naturally soften at most 0.74 MPa week–1 within 72 weeks. Abstract: 300 MPa grade biodegradable Zn-(0.6, 0.8)Mn-(< 0.1)Mg alloys with yield strengths > 300 MPa and elongations > 15% have been developed, which are designated as Zn06Mn006Mg (HE) and Zn08Mn005Mg (HE) in as-extruded state. They are the newest members of a small group of biodegradable Zn alloys with mechanical properties beyond the generally accepted benchmark for orthopedic implants. Immersed in simulated body fluid for 30 days, Zn06Mn006Mg (HE) and Zn08Mn005Mg (HE) exhibit corrosion rates of 38 and 53 µm y –1, respectively. They show high antibacterial rates of 93%–97% against E. coli . In 25%–75% extracts of both the alloys, MC3T3-E1 cell viabilities for 1 day and 3 days are all over 100%, indicating complete cytocompatibility. In 100% extracts for 3 days, both alloys show non-toxicity. After a longtime room temperature storage of 72 weeks, natural embrittling alike Zn-Mg alloys does not happen. The Zn-Mn-Mg alloys still have mechanical properties exceeding the benchmark by a large margin. The in vitro study shows the newly developed BHSDLA Zn-Mn-Mg alloys are promising candidates for orthopedic implants. Graphical abstract: Image, graphical abstract